EFFECTIVENESS OF A NUTRITIONAL COUNSELING PROGRAM AMONG PATIENTS WITH TYPE 2 DIABETES IN TAN THOI HIEP WARD, HO CHI MINH CITY: A PRE–POST INTERVENTION STUDY (Vietnam Journal of Community Medicine, 2026)
Objective: To assess dietary adherence and fasting blood glucose control in patients with type 2 diabetes before and after a nutrition counseling intervention at Tan Thoi Hiep Ward Health Station in 2025.Method: A Pre–Post intervention study was conducted on 101 outpatients with type 2 diabetes in 2025. Participants were interviewed using the Perceived Dietary Adherence Questionnaire (PDAQ) to assess dietary adherence.Results: The mean age of participants was 62 ± 11.4 years; females accounted for 60.4%, and 95.1% lived with family members. The proportion of participants with disease duration from 1 to under 5 years was 49.5%; 78.2% had a family history of diabetes, and 93.1% had comorbidities. The proportion of participants with good dietary adherence increased from 29.7% to 83.2% after one month. Across the nine PDAQ components, the rate of good adherence increased markedly, from 30.7% - 38.6% before counseling to 74.3% - 89.1% after counseling. The proportion of participants with good fasting glucose control increased from 9.9% to 45.5% after counseling (p < 0.001).Conclusion: Nutrition counseling was associated with marked improvements in dietary adherence and fasting glucose control among outpatients with type 2 diabetes. Routine and individualized nutrition counseling should be strengthened and integrated into outpatient diabetes management at the primary care level.
Keywords: Type 2 diabetes, dietary adherence, PDAQ, nutrition counseling.